Engineering the active site of ascorbate peroxidase. (May 2001) - Raven, E. Lloyd; Celik, A.; Cullis, P. M.; Sangar, R.; Sutcliffe, M. J.
Abstract : Understanding the catalytic versatility of haem enzymes, and in particular the relationships that exist between different classes of haem-containing proteins and the mechanisms by which the apo-protein structure controls chemical reactivity, presents a major experimental and theoretical challenge. These issues are discussed in the general context of peroxidase and cytochrome P450 chemistry, and specific issues relating to the catalytic chemistry of ascorbate peroxidase are highlighted.